80 Hours operation of a tubular solid oxide fuel cell using propane/air. (15th August 2020) - Chen, Yu; Lu, Minyi; Yang, Huazheng; Yao, Yingbang; Tao, Tao; Lu, Shengguo; Wang, Chao; Ramesh, Rajendran; Kendall, Michaela; Kendall, Kevin; Ouyang, Xiaoping; Liang, Bo
Highlights: The foam ceramic reformer with Ni-Fe nanosheets catalyst were embedded in a TSOFC. Using propane as fuel, the cell was operated for more than 100 h. Before 80 h, the power degradation rate is acceptably low. Sulfur element was found at the anode/electrolyte interface. Abstract: High power density and simple design are vital for these fuel cell-based portable power generation devices. This study provides an 8.6 g tubular SOFC with embedded a catalytic partial oxidation reformer, which is fabricated and operated for more than 100 h using propane/air. Nickel-iron nanosheets, as catalysts for reforming, supported on α-Al2 O3 foam ceramic are synthesized by hydrothermal treatment. Testing for 80 h gives a power degradation of about 20% compared with the initial value. It is mainly attributed to sulfur-poisoning of nickel near anode/electrolyte interface according to transmission electron microscope (TEM) analysis. From TEM/energy dispersive spectroscopy line-scan results across the anode/electrolyte interface, sulfur as either aggregate at the nickel/yttria-stabilized zirconia grain boundaries or on the nickel grain surface, and no obvious carbon phase is founded. The maximum power density is 0.67 W cm −2 at 700 °C using propane/air (12 vol% propane), about 5% higher than the same cell using 20 vol% hydrogen.